The other woman [compact disc, unabridged] - Silva, Daniel, 1960- (Silva, Daniel, 1960- Gabriel Allon series., 2018)
In an isolated village in the mountains of Andalusia, a mysterious Frenchwoman begins work on a dangerous memoir. It is the story of a man she once loved in the Beirut of old, and a child taken from her in treason's name. The woman is the keeper of the Kremlin's most closely guarded secret. Long ago, the KGB inserted a mole into the heart of the West - a mole who stands on the doorstep of ultimate power. Only one man can unravel the conspiracy: Gabriel Allon, the legendary art restorer and assassin who serves as the chief of Israel's vaunted secret intelligence service. Gabriel has battled the dark forces of the new Russia before, at great personal cost. Now he and the Russians will engage in a final epic showdown, with the fate of the postwar global order hanging in the balance. Gabriel is lured into the hunt for the traitor after his most important asset inside Russian intelligence is brutally assassinated while trying to defect in Vienna.